The socioeconomic status indicator (SES): a systematic and exploratory lit-erature review (PerCursos, 2023)
Socioeconomic measures play a fundamental role in elaborating diagnoses of the socioeconomic environment, providing a study parameter in sociology, demography, economics, and political science. Due to its relevance, this study aims to identify what the national and international scientific literature presents about the socioeconomic level (SES) indicator so that it is possible to highlight the main results, recommendations, problems, and future research opportunities in measuring the indicator. A systematic review was carried out to achieve the objectives, complemented by an exploratory search based on the SSF (Systematic Search Flow) method. From the review, the following results stand out: the studies seek to operationalize the measurement of the socioeconomic indicator through components of parents' education, parents' occupational prestige, and family income or wealth; the evolution of the NSE measure is in line with the use of statistical models from the Item Response Theory (IRT). It is concluded that the construct's definition is shaped according to the different realities of each country.
Keywords: socioeconomic status indicator; consumer goods; IRT; socio-economic indicators